Debussy's forms of deception : toward a theory of implication, attraction, and tension in the Préludes - Shanahan, Daniel Thomas (Trinity College (Dublin, Ireland). Department of Music, 2011)
This thesis examines the role of process in Debussy’s music through analyses of melodic implication, rhythmic projection, and harmonic attraction in the Preludes. It traces the evolution of analytical methodologies that have been applied to the composer’s music, focusing on their treatment of ambiguity in the composer’s music. It then argues for an approach that focuses on the potentialities of the various parameters, with the aim of viewing the interaction of elements of process and closure throughout the selected pieces.
Keywords: Music, Ph.D.; Ph.D. Trinity College Dublin